(untitled) (International Journal of Engineering and Computer Science, 2015)
In recent years data hiding has been proposed as a likely technique for the purpose of information security.Hiding data is the process of embedding information into digital content without causing perceptual degradation. In data hiding, pieces of information represented by some data are hidden in a cover media like image. The main intention of data hiding is to prevent the detection of hidden information.The most commonly used algorithm for data hiding is Least Significant Bit algorithm apart from these various algorithms have been proposed for data hiding in last few years. This paper consists of survey of different methods and techniques available for data hiding